Epitope specific T‐cell responses against influenza A in a healthy population. Issue 2 (8th December 2015) - Savic, Miloje; Dembinski, Jennifer L.; Kim, Yohan; Tunheim, Gro; Cox, Rebecca J.; Oftung, Fredrik; Peters, Bjoern; Mjaaland, Siri
Summary: Pre‐existing human CD4 + and CD8 + T‐cell‐mediated immunity may be a useful correlate of protection against severe influenza disease. Identification and evaluation of common epitopes recognized by T cells with broad cross‐reactivity is therefore important to guide universal influenza vaccine development, and to monitor immunological preparedness against pandemics. We have retrieved an optimal combination of MHC class I and class II restricted epitopes from the Immune Epitope Database (www.iedb.org ), by defining a fitness score function depending on prevalence, sequence conservancy and HLA super‐type coverage. Optimized libraries of CD4 + and CD8 + T‐cell epitopes were selected from influenza antigens commonly present in seasonal and pandemic influenza strains from 1934 to 2009. These epitope pools were used to characterize human T‐cell responses in healthy donors using interferon‐ γ ELISPOT assays. Upon stimulation, significant CD4 + and CD8 + T‐cell responses were induced, primarily recognizing epitopes from the conserved viral core proteins. Furthermore, the CD4 + and CD8 + T cells were phenotypically characterized regarding functionality, cytotoxic potential and memory phenotype using flow cytometry. Optimized sets of T‐cell peptide epitopes may be a useful tool to monitor the efficacy of clinical trials, the immune status of a population to predict immunological preparedness against pandemics, as well as being candidates for universal influenza vaccines.